App-supported sleep coaching: implications for sleep duration and sleep quality - Gorovoy, Suzanne B.; Campbell, Rebecca L.; Fox, Rina S.; Grandner, Michael A. (Frontiers in Sleep, 2023)
Objectives The present study evaluated whether completers of a 12-week app-based, personalized text supported sleep coaching program demonstrated improvements in sleep continuity, sleep duration, and reduced use of sleep aids. Methods Data were obtained from Sleep Reset, a 12-week consumer product that offers app-based sleep education and monitoring, along with personalized text-based sleep coaching provided by live coaches. Five hundred sixty-four completers were included in the study. Pre-post changes for sleep latency (SL), wake after sleep onset (WASO), number of awakenings (NWAK), total sleep time (TST), sleep efficiency (SE%) and use of “sleep aids” were evaluated. To evaluate whether the program produced meaningful results, the proportion of participants who demonstrated reductions in SL, WASO, and NWAK, and increases in TST and SE% were examined. Results Mean SL was reduced by 11 min, mean WASO was reduced by 28 min, mean SE% increased by 6.6%, and mean TST increased by about 44 min. Of those who reported using “sleep aids” during Week 1, 41% no longer used them by week 12. Those with low SE% at baseline demonstrated greater improvements in SL (16.2 vs. 5.7 min), WASO (47.3 vs. 7.2 min), SE% (11.2 vs. 1.6%), and TST (65.3 vs. 31.2 min). Those with ≤ 6 h of sleep at baseline demonstrated greater improvements in WASO (36.8 vs. 22.3 min), SE% (10.1 vs. 4.3%), and TST (85.1 vs. 25.5 min). Conclusion Participants that completed the app-based, personalized text supported coaching intervention reported subjective improvements in sleep duration and quality that suggest more beneficial effects particularly in those with lower sleep efficiency or sleep duration at baseline. An effective sleep coaching program that utilizes trained sleep coaches with access to board-certified providers, may provide a valuable resource for subclinical populations.